Analisis Yuridis terhadap Pelaksanaan Fungsi Pembinaan dan Pengamanan oleh Kantor Wilayah Direktorat Jenderal Pemasyarakatan Bengkulu - Praja Ganda Agung; Reza Seby Alfikri; Muhammad Azizul Fajri; Ganefi (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
This study analyzes the implementation of correctional guidance and security functions by the Regional Office of the Directorate General of Corrections in Bengkulu from the perspective of positive law. These functions are an integral part of the correctional system, aimed at developing the personality, independence, and social reintegration of inmates, while simultaneously maintaining the security and order of correctional facilities. The study employs a normative juridical approach using a statute approach, analyzing the prevailing legislation as the legal basis for the implementation of correctional guidance and security functions. The findings indicate that the Bengkulu Regional Office implements guidance functions through programs for developing inmates’ independence, vocational training, and virtual exhibitions of inmates’ work, while security functions are actualized through supervision, patrols, control measures, and coordination among correctional units. These functions are carried out in accordance with valid legal foundations, including Law Number 22 of 2022 on Corrections, Government Regulation Number 31 of 1999, and Minister of Immigration and Corrections Regulation Number 4 of 2024. The study recommends enhancing human resource capacity, routinely evaluating guidance programs, and developing innovative approaches to ensure that correctional operations are effective, secure, and beneficial to society.